Nanomedicine: Bioavailability, Biotransformation and Biokinetics - Ravindran, Selvan; Tambe, Amlesh J.; Suthar, Jitendra K.; Chahar, Digamber S.; Fernandes, Joyleen M.; Desai, Vedika (Current Drug Metabolism, 2019)
Background: Nanomedicine is increasingly used to treat various ailments. Biocompatibility of nanomedicine is primarily governed by its properties such as bioavailability, biotransformation and biokinetics. One of the major advantages of nanomedicine is enhanced bioavailability of drugs. Biotransformation of nanomedicine is important to understand the pharmacological effects of nanomedicine. Biokinetics includes both pharmacokinetics and toxicokinetics of nanomedicine. Physicochemical parameters of nanomaterials have extensive influence on bioavailability, biotransformation and biokinetics of nanomedicine. Methods: We carried out a structured peer-reviewed research literature survey and analysis using bibliographic databases. Results: Eighty papers were included in the review. Papers dealing with bioavailability, biotransformation and biokinetics of nanomedicine are found and reviewed. Bioavailability and biotransformation along with biokinetics are three major factors that determine the biological fate of nanomedicine. Extensive research work has been done for drugs of micron size but studies on nanomedicine are scarce. Therefore, more emphasis in this review is given on the bioavailability and biotransformation of nanomedicine along with biokinetics. Conclusion: Bioavailability results based on various nanomedicine are summarized in the present work. Biotransformation of nanodrugs as well as nanoformulations is also the focus of this article. Both in vitro and in vivo biotransformation studies on nanodrugs and its excipients are necessary to know the effect of metabolites formed. Biokinetics of nanomedicine is captured in details that are complimentary to bioavailability and biotransformation. Nanomedicine has the potential to be developed as a personalized medicine once its physicochemical properties and its effect on biological system are well understood.
Keywords: bioavailability